Leveraging Blockchain for Ethical Business Operations : A Bibiometric Analysis - Mi’rojul Azkiyyah; Nurul Asfiah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This article explores the application of blockchain technology to enhance ethical operations in the food industry. Blockchain is viewed as a potential solution for improving transparency, accountability, and efficiency in the food supply chain. This technology enables the recording of transactions that are immutable and publicly verifiable, reducing the likelihood of fraud and product contamination. Additionally, blockchain can support compliance with ethical and sustainability standards, helping companies build trust with consumers. The study suggests that further research is needed to explore various aspects of blockchain application in the food industry, such as sustainable finance, digital forensics, and supply chain management. However, the article is limited by its focus on bibliometric analysis and lacks empirical data on blockchain implementation in the food industry. Future research should combine theoretical and practical approaches to provide a comprehensive view of blockchain's use in ethical and sustainable business operations.